دور الموانئ الجزائرية في التجارة الخارجية خلال العهد العثماني (1519-1830م) ميناء مدينة الجزائر أنموذجا - زهير نادية (جامعة محمد بوضياف بالمسيلة, 2025)
لعب ميناء مدينة الجزائر خلال العهد العثماني (1519-1830م)، بدور بالغ الأهمية في التجارة الخارجية للمنطقة، بحيث لم يكن هذا الميناء مجرد نقطة عبور للبضائع، بل كان مراكز حيويا للتبادل التجاري، والقوة البحرية، ونقطة وصل رئيسية تربط شمال إفريقيا بأوروبا والمشرق العربي، تنوعت الواردات إلى ميناء الجزائر لتشمل الأقمشة، التوابل، السلع المصنعة، المعادن، والحبوب. في المقابل، صدرت الجزائر عبر هذا الميناء منتجاتها المحلية كالصوف، الجلود، الشموع، الزيوت، وبعض المنتجات الزراعية. خضعت التجارة في الميناء لتنظيم دقيق من قبل السلطات العثمانية في الجزائر. فُرضت رسوم جمركية على الواردات والصادرات، مما أسهم في تعزيز إيرادات الخزينة. كما فُرضت رقابة صارمة على جودة البضائع والأسعار لضمان استقرار السوق. The port of Algiers played a highly significant role in the region’s foreign trade during the Ottoman era (1519–1830); This sea port was not merely a transit point for goods but a vital center for trade exchange, naval power, and a main link connecting North Africa with Europe and the Arab East. Imports to the port of Algiers included textiles, spices, manufactured goods, metals, and grains. In return, Algeria exported its local products through this port, such as wool, leather, candles, oils, and some agricultural products. Trade at the port was strictly regulated by the Ottoman authorities in Algiers. Customs duties were imposed on imports and exports, contributing to the treasury's revenues. Strict control was also enforced on the quality of goods and pricing to ensure market stability.